Heart rate, technical performance, and session-RPE in elite youth soccer small-sided games played with wildcard players - Sanchez-Sanchez, J.; Hernandez, D.; Casamichana, D.; Martinez-Salazar, C.; Ramirez-Campillo, R.; Sampaio, J. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to compare heart rate (HR), rating of perceived exertion (RPE), and technical-tactical actions during small-sided games (SSGs) played without (CTR), with internal (IW), and with IW and external (IEW) wildcard players. A total of 22 young male soccer players (age 17.2 ± 0.9 years) randomly completed six 4vs4 SSG situations. The control conditions occurred with goals scored without goalkeeper (4vs4-NO) and with goalkeeper (4vs4-GK). During the experimental conditions, the situations incorporated 2 IW (4vs4+2IW-NO, 4vs4+2IW-GK) and 2 IEW (4vs4+2IW+2IEW-NO, 4vs4+2IW+2IEW-GK). Processed results did not include data from goalkeepers, IW, and IEW players. The HR was divided in intensity-zones (Z1, Z2, and Z3, for <80%, 80-90%, and >90% of maximal HR, respectively) and the analyzed technical-tactical actions were the pass, dribbling, collective success, and pause. The effects of IW and IEW were analyzed through repeated measures analysis of variance. During 4vs4+2IW+2IEW-NO, greater time was recorded in Z1 (p = 0.05) compared with 4vs4-NO and 4s4+2IW-NO. During 4vs4+2IW+2IEW-GK, greater time was recorded in Z1 and less in Z3 (p = 0.05) compared with 4vs4-GK. Greater RPE was reported in 4vs4-NO (p < 0.01) and 4vs4+2IW-NO (p < 0.01) compared with 4vs4+2IW+2IEW-NO, and during 4vs4-GK (p < 0.01) than 4vs4+2IW+2IEW-GK. Greater number of dribbling situations were recorded during 4vs4-NO (p = 0.05) compared with 4vs4+2IW+2IEW-NO. In conclusion, compared with the control condition of 4vs4, the incorporation of IEW reduced HR, RPE, and dribbling actions.